Impact of thermoneutral acclimation on a murine model of polymicrobial peritonitis - Goldia Chan; Christopher Fry; Jean Nemzek (PLoS ONE, 2025)
To examine the effects of ambient temperature on the reproducibility and translation of a murine sepsis model, we hypothesized that acclimation of mice in temperatures within their thermoneutral zone would alter immune responses and outcomes compared to standard housing temperatures. Mice housed for one week in thermoneutral (30°C) as compared to standard (22°C) conditions displayed lower counts of circulating neutrophils (0.52 ± 0.20 vs. 1.10 ± 0.54 x103/μL; p = 0.011) and peritoneal macrophages (0.80 ± 0.57 vs. 1.62 ± 0.62 x 105/μL; p = 0.002) as well as reduced in vitro production of IFN-γ by stimulated splenocytes (0.38 ± 0.68 vs 2.55 ± 0.76 x104 pg/mL, respectively, p = 0.004). After one week of temperature acclimation followed by CLP, the 7-day mortality was significantly lower under thermoneutral as compared to standard temperatures (80% vs 30%, respectively; p = 0.012), although core body temperature was preserved (average for 24 hours: 36.4 ± 1.3°C vs 31.7 ± 4.7°C; p < 0.0001). The lower survival was accompanied by increased systemic IL-6 levels (3.8 ± 3.3 vs 1.9 ± 1.3 x103 pg/mL; p = 0.04) and less robust influx of neutrophils into the peritoneum (1.68 ± 1.07 vs. 4.20 ± 2.46 x105/μL, respectively; p = 0.0003). Overall, thermoneutral temperatures impacted innate immune parameters before and after CLP, producing distinctly different outcomes. Therefore, ambient temperature is an important variable that could impact model reproducibility and should be reported for the acclimation period and experimentation phases of murine sepsis studies.